MEMS in space. - Cass, S. (IEEE spectrum)
The satellite industry could experience its biggest revolution since it joined the ranks of commerce, thanks to some of the smallest machines in existence. Researchers are performing experiments designed to convince the aerospace industry that microelectromechanical systems (MEMS) could open the door to low-cost, high-reliability, mass-produced satellites. MEMS combine conventional semiconductor electronics with beams, gears, levers, switches, accelerometers, diaphragms, microfluidic thrusters, and heat controllers, all of them microscopic in size. Some of the advantages of using MEMS-based satellites are low launch costs and high resistance to radiation and vibration. MEMS-based satellites also promise to be cheaper to develop and fabricate than conventional spacecraft